Effects of Warming Up With Music on Moods and Training Motivation among Athletes - Khazdozi, Golnaz; Bahari, Seyyed Mohiadin; Ashayeri, Hassan (Revista Administração em Diálogo - RAD, 2017)
The purpose of the present study is to review the effects of warming up with music on moods and training motivation among Kurdistan province’s female handball players0 for this purpose, 24 handball players of premier league of Kurdistan province were selected as the research subjects through a random sampling method. In this study a pretest-posttest design is applied by which 12 subjects have been selected as control group and 12 as experimental group. The latter group performed warm ups free from music. For the purpose of estimation of motivation of subjects, the questionnaire of sports motivation was made use of. In addition, for investigation of the moods variable, the questionnaire of athletes’ moods was used. Research results using the statistical test of Mann-Whitney showed that no significant difference existed between the experimental and control groups’ motivation and moods after performance of the warming up program (P: 0.124). This was while there was a statistically significant difference between the experimental and control groups’ moods prior and post to execution of Training program (P= 0.003). In general, it may be concluded that playing music doesn’t have any significant effects on athletes’ motivation while their moods can undergo significant changes through listening to music during warming up.